HUBUNGAN DUKUNGAN KELUARGA DENGAN KEMANDIRIAN DALAM KEHIDUPAN SEHARI-HARI ANAK TUNAGRAHITA DI SEKOLAH KHUSUS YKDW 01 KARAWACI TANGERANG - Indahwati, Sri; Haeriyah, Siti; Ratnasari, Febi (Nusantara Hasana Berdikari, 2022)
Independence is important for deaf children and needs to be trained as early as possible so that children do not rely excessively on others. It is also feared that if not taught independently from an early age children with tunagrahita are unable to take care of themselves, cannot get along with the community or cannot do something for their lives in the future. Family support is very important for children with tunagrahita, because if they do not get support from family or the environment will cause obstacles to their development and independence. Research objectives to find out whether there is a relationship of family support with independence in the daily life of tunagrahita Children in School of YKDW 01 Karawaci Tangerang year 2021. This type of research uses quantitative research design with a Cross Sectional approach. The sampling technique used by this study is a saturated accidental sampling with a sample number of 63 respondents. There is a relationship between family support and independence in the daily life of tunagrahita children.